Assessment of Microbiological Quality, Nutrient Composition, and Physical Characteristics in Groundnut Flour (nsinjiro) Sold in Local Markets in Central and Southern Regions of Malawi - Allan Basikolo; Dickson Mbeya (CV Media Inti Teknologi, 2025)
Background of study: Malawi produces groundnuts for consumption, trade, and animal feed. Microbiological quality, nutrient composition, physical properties, in groundnut flour sold in Malawian markets had not been identified and studied extensively. Therefore, their nature and extent of distribution needed to be documented as the basis for intervention programs in Malawi.Aims and scope of paper: To assess Microbiological Quality, Nutrient composition, and Physical Characteristics in Groundnut Flour sold in Local markets in Central and Southern Regions of Malawi.Methods: In the Central, 16 samples were purchased of 32 while in the Southern region, 22 samples were purchased of 39 respectively. Samples were stored in a deep freezer at 4 OC for 26 days pending analysis. Later samples were analyzed using multiple standard methods and the data were analyzed using SPSS.Result: 18.42% of samples contained E. coli ranging from 0 to 30 cfu/g, and 13.16% contained Salmonella ranging from 0 to 70 cfu/g, and these exceeded the permissible limits for Malawi and the International Commission on Microbiological Standards for Foods. The limit for Malawi is 10,000 cfu/g, while the ICMSF is 500,000 cfu/g. They contained protein (30.67%), carbohydrate (37.87%), fat (43.90%), and ash (3.43%). They were light in color with L* (49.79-59.88).Conclusion: The results indicated that the groundnut flour studied was susceptible to microbial contamination, hence, hygienic monitoring before marketing is required. Policy enactment for sanitary practices, and enforcement of standards to reduce the menace of microbes and avoid food-borne diseases among the populace is required.